Confinement effects in protonation reactions catalyzed by zeolites with large void structures - Zalazar, María Fernanda (2018)
Fil: Zalazar, María Fernanda. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.